Case Report: Long-Term Suppression of Paroxysmal Kinesigenic Dyskinesia After Bilateral Thalamotomy - Murakami, Masato; Horisawa, Shiro; Azuma, Kenko; Akagawa, Hiroyuki; Nonaka, Taku; Kawamata, Takakazu; Taira, Takaomi (Frontiers in Neurology, 2021)
Background: Paroxysmal kinesigenic dyskinesia (PKD) is a movement disorder characterized by transient dyskinetic movements, including dystonia, chorea, or both, triggered by sudden voluntary movements. Carbamazepine and other antiepileptic drugs (AEDs) are widely used in the treatment of PKD, and they provide complete remission in 80–90% of medically treated patients. However, the adverse effects of AEDs include drowsiness and dizziness, which interfere with patients' daily lives. For those with poor compatibility with AEDs, other treatment approaches are warranted. Case Report: A 19-year-old man presented to our institute with right hand and foot dyskinesia. He had a significant family history of PKD; his uncle, grandfather, and grandfather's brother had PKD. The patient first experienced paroxysmal involuntary left hand and toe flexion with left forearm pronation triggered by sudden voluntary movements at the age of 14. Carbamazepine (100 mg/day) was prescribed, which led to a significant reduction in the frequency of attacks. However, carbamazepine induced drowsiness, which significantly interfered with his daily life, especially school life. He underwent right-sided ventro-oral (Vo) thalamotomy at the age of 15, which resulted in complete resolution of PKD attacks immediately after the surgery. Four months after the thalamotomy, he developed right elbow, hand, and toe flexion. He underwent left-sided Vo thalamotomy at the age of 19. Immediately after the surgery, the PKD attacks resolved completely. However, mild dysarthria developed, which spontaneously resolved within three months. Left-sided PKD attacks never developed six years after the right Vo thalamotomy, and right-sided PKD attacks never developed two years after the left Vo thalamotomy without medication. Conclusion: The present case showed long-term suppression of bilateral PKDs after bilateral thalamotomy, which led to drug-free conditions.